2016
DOI: 10.2147/dddt.s102189
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intrauterine exposure to immunosuppressive treatment on changes in the immune system in juvenile Wistar rats

Abstract: BackgroundIn our study, we assessed the impact of immunosuppressive drug combinations on changes in the immune system of juvenile Wistar rats exposed to these drugs during pregnancy. We primarily concentrated on changes in two organs of the immune system – the thymus and the spleen.MethodsThe study was conducted on 40 (32+8) female Wistar rats administered full and half dose of drugs, respectively, subjected to regimens commonly used in therapy of human kidney transplant recipients ([1] cyclosporine A, mycophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…New studies are needed to evaluate the effects of different dosages in different time spans. The drug dosages used were based on previous studies [ 7 8 ]. However, monitoring immunosuppressive activity may be useful in assessing toxicity and efficiency of drugs used in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New studies are needed to evaluate the effects of different dosages in different time spans. The drug dosages used were based on previous studies [ 7 8 ]. However, monitoring immunosuppressive activity may be useful in assessing toxicity and efficiency of drugs used in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The drug dosages were calculated according to data found in the cited literature [ 7 8 ]. While TAC is toxic in high doses, 0.1–10 mg/kg/day dosages of TAC have been administered for different purposes and its use reported in various studies.…”
Section: Methodsmentioning
confidence: 99%
“…Kabat-Koperska et al [ 47 ] indicated qualitative, quantitative, and morphological changes in the immune system of infant rats born to pharmacologically immunosuppressed females. The thymus structure, spleen composition, and splenocyte IL-17 production were mostly affected in a drug regimen-dependent manner [ 47 ]. It should be also emphasised that CNIs disturb oxidative stress.…”
Section: Classes Of Immunosuppressive Drugsmentioning
confidence: 99%
“…Wang et al [ 67 ] suggest that glycyrrihizic acid and prednisone improve renal function, relieve the renal morphological changes, and decrease interstitial fibrosis in rats [ 67 ]. However, some researchers, based on the examination of immunosuppressive regimens, where prednisone was included, indicated the severe effect of these drugs on various tissues, including kidney [ 46 , 47 , 52 ]. Nevertheless, these studies concerned triple-drug protocols; therefore, the role of prednisone on organs was not clear [ 46 , 47 , 52 ].…”
Section: Classes Of Immunosuppressive Drugsmentioning
confidence: 99%
See 1 more Smart Citation